A Portrayal of Farmers in Nepali Broadsheet Dailies - Dhakal, Mod (JMC Research Journal, 2020)
This article attempts to explore the portrayal of Nepali farmers in the Nepali dailies. It explores the situation of the agricultural landscape in Nepal and the picture of Nepali peasants painted by the Nepali dailies. The revelation of the portrayal of farmers in Nepali broadsheet dailies is based on a thorough analysis of contents for the period of 16 days that appeared in three major 'national' broadsheet dailies published from the Capital city Kathmandu. The analysis of the news and opinion articles on agriculture and farmers reveals that merely 2.12 % of the total news was on agriculture while only 10 items were particularly about farmers and just seven portrayed farmers in a positive light. Compared against the 66 per cent of the population engaged in agriculture and its 28.2 % contribution to the economy, it's an injustice to farming and farmers. The study shows that the number of items that showed concerns to the farmers' plight are so nascent that they would barely make any impact. The picture of agriculture as painted by the major broadsheets is gloomy, arduous, complex, and less profitable. The social attitude on farmers carried by the media is they are poor, sad, and neglected human beings living in a hope that someday they will be able to get the inputs with government subsidy. Nepali newspapers have solidified the image of farmers as dirty and living in poor houses waiting for some external support or intervention to rescue them, like the studies found in other societies.